Integration of Environmental Management to Local Policy Makers’ Priority Agenda: The Bukidnon State University Experience - Mirasol, Joy M.; Itaas, Estela C. (JPAIR Multidisciplinary Research, 2008)
The Bukidnon State University (BSU) signed a memorandum of agreement with Tanggol Kalikasan (TK), an organization of lawyers and environmentalists. One of its aims is to jointly promote sound environmental governance utilizing lessons learned in Protected Area Management in the province. BSU upholds its commitment to extend services for the environment, thus cater the venue of the Institute of Environmental Governance (IEG), in partnership with other agencies to conduct capacity development that will guide local policy makers on the integration environmental governance as part of their priority agenda. The training design addressed the variability of the educational status of the province’ local environmental key players and likewise, formulated the environmental entry plan among local policy makers. Result of the initial implementation identified some challenges that include among others, the absence of platform to increase public access to environmental information, aggressive, coordinated and collaborated environmental law enforcement, sustained financing for environmental management and governance and increasing the number of champions to impart knowledge to the remotest part of the locality where the action is. Initial result of the assessment revealed that, local policy makers recommended and recognized the need to make mandatory the creation of the Municipal and City environment and Natural resources Offices and inclusion of environmental protection as part of the devolved functions down to the barangay level in the local government code.